PENERAPAN MODEL SCRIPT PADA MATERI KEKAYAAN SUMBER ENERGI DI INDONESIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 11 PIDIE - Zahrina (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2020)
This study aim at identifying the use of Script to increase fourth grade students’ achievement of MIN 11 Pidie in learning the topic: Source of Energy in Indonesia. The subject was fourth grade students of MIN 11 Pidie. The number of the students were 20, consist of 7 females and 13 males. The technique of collecting data used were test, observation and field notes. The result indicated that students’ learning achievement increased in each cycle: cycle I : 15%, cycle II : 60%, and cycle III : 100%. Therefore, it can be concluded that the use of Script in learning could improve student’s achievement in learning and also improve teacher’s capability in teaching.